Native structure of a type IV secretion system core complex essential for Legionella pathogenesis - Kubori, Tomoko (National Academy of Sciences, 2014)
Bacterial type IV secretion systems are evolutionarily related to conjugation systems and play a pivotal role in infection by delivering numerous virulence factors into host cells. Using transmission electron microscopy, we report the native molecular structure of the core complex of the Dot/Icm type IV secretion system encoded by Legionella pneumophila, an intracellular human pathogen. The biochemically isolated core complex, composed of at least five proteins—DotC, DotD, DotF, DotG, and DotH—has a ring-shaped structure. Intriguingly, morphologically distinct premature complexes are formed in the absence of DotG or DotF. Our data suggest that DotG forms a central channel spanning inner and outer membranes. DotF, a component dispensable for type IV secretion, plays a role in efficient embedment of DotG into the functional core complex. These results highlight a common scheme for the biogenesis of transport machinery.